MULTIMEDIA COMPLEX ON THE PRINCIPLE OF CREATING A MAGNETIC FIELD IN AN ASYNCHRONOUS ELECTRIC MOTOR - V. P. Belyaev; V. A. Shiyan (Системный анализ и прикладная информатика)
Thanks to the development of computer technologies, information and technical means give positive results in the educational process. The created training complexes of the studied material increase the quality of its perception. The article considers the use of computer graphics on the example of creating an electronic multimedia complex of an interactive nature. The multimedia complex realizes three basic principles of multimedia: the presentation of information through a combination of many perceived environments; presence of several storylines in the content of the product; Artistic design of the interface and navigation tools. We used an HTML-based shell plus JavaScrip and a collection of multimedia work – Adobe Flash plus ActionScript.